Women in law : a bio-bibliographical sourcebook - Salokar, Rebecca Mae, 1956-; Volcansek, Mary L., 1948- (Westport, Conn. : Greenwood Press, 1996)
Includes profiles women who have made major contributions to the law through their work in the legal profession, scholarly legal research, and political activism directed at socio-legal reforms.
Introduction / Mary L. Volcansek -- Florence Ellinwood Allen / Sarah Wilson -- Mary Arden / Donald W. Jackson -- Anita Augsburg / Mary L. Volcansek and Luba DeWitt -- Suzanne Bastid-Basdevant / Jacqueline Lucienne Lafon -- Miriam Ben-Porat / Martin Edelman -- Myra Bradwell / Mary L. Volcansek -- Beverly Blair Cook / Lee Epstein -- Irene R. Cortes / C. Neal Tate -- Takako Doi / William B. Cleary -- Ruth Bader Ginsburg / Rebecca Mae Salokar -- Brenda Marjorie Hale / Donald W. Jackson -- Rosalyn Higgins / Donald W. Jackson -- Leonilde Iotti / Maria Elisabetta de Franciscis -- Barbara Charline Jordan / Cassandra R. Veney -- Sylvie Kanigi / Kevin Hill -- Carrie Burnham Kilgore / Greg Casey -- Helen Kinnear / Marie Corbett and Doris Corbett -- Claire L'Heureux-Dube / Teresa Scassa -- Jutta Limbach / Donald P. Kommers -- Burnita Shelton Matthews / Cynthia Harrison -- Beverley McLachlin / C. Lynn Smith -- Soia Mentschikoff / Zipporah Batshaw Wiseman.
Includes bibliographical references (pages 353-356) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Women lawyers -- Biography; Women judges -- Biography; Women law teachers -- Biography; Women political activists -- Biography; Women -- Political activity -- Biography; Law -- Bio-bibliography.; Avocates -- Biographies; Femmes juges -- Biographies; Professeures de droit -- Biographies; Femmes activistes -- Biographies; Femmes -- Activité politique -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- General; REFERENCE -- Bibliographies & Indexes; Law; Women judges; Women law teachers; Women lawyers; Women political activists; Women -- Political activity; Avocates -- Biographies; Femmes juges -- Biographies; Professeurs de droit -- Biographies; Femmes professeurs (enseignement supérieur) -- Biographies; Femmes -- Activité politique -- Biographies; Droit -- Biobibliographie; collective biographies; bibliographies; Bibliographies; Bio-bibliography; Biographies; Biographies; Bibliographies; Biographies; Bibliographies